From delay to payday: Easing bureaucrat access to implementation information strengthens social protection delivery - Eric Dodge; Yusuf Neggers; Rohini Pande; Charity Troyer Moore (Yale University, Economic Growth Center, 2025)
Poor implementation frequently impedes social protection delivery in low-state-capacity settings. In such environments, reducing managers' information acquisition costs may improve their grasp of frontline issues and program performance. However, in the presence of managerial rent-seeking, increasing the principal's information may be key, and doing so just for managers can backfire. To assess this trade-off and implications for program performance, we collaborated with two Indian states to randomly vary bureaucrat access to PayDash, a digital platform for real-time tracking of worker payment processing for the national rural workfare program. In treated districts, PayDash expedited bureaucrat processing of workfare payments by 17%, and increased available worksites and participating household work days by 23% and 10%, respectively. Work provision rose relatively more during the agricultural lean season. PayDash has the same impact when offered to principals as to managers, and no further gains when offered to both, indicating that manager effort to acquire information constrains implementation. Consistent with information allowing principals to better condition performance incentives on managerial effort, PayDash for principals reduced manager posting transfers by 24%. PayDash strengthened state capacity at a considerably lower cost than hiring staff, while benefiting rural Indians by more than 170 times the costs.
Keywords: C93; D73; I38; M59; O15; 330